Extensive literature search on mineral oil hydrocarbons. Issue 2 (24th February 2023) - Licht, Oliver; Breuer, Franziska; Blümlein, Katharina; Schwonbeck, Susanne; Pallapies, Dirk; Kellner, Rupert; Wiedemeier, Petra; Bitsch, Annette
Abstract: An Extensive Literature Search (ELS) to collect and identify all studies published since 2010 and relevant to the topic mineral oil hydrocarbons in combination with the substance group characterisation, occurrence in food and toxicity was performed in the three databases PubMed, Web of Science and SciFinder® for six Areas. After combination of the searches from the three databases and removal of the duplicates, the total number of references is 2504. The evaluation of all retrieved references for relevance by screening the title and abstract and applying eligibility criteria (inclusion/exclusion) resulted in a total number of relevant references for Area 1 of 55, for Area 2 of 27, for Area 3 of 15, for Area 4 of 21 for Area 5 of 1 and for Area 6 of 6. The total number of relevant references was 93. However, for the substance group POH no relevant reference was identified. Additionally, there are 4 references additionally, which could not be clearly assigned.